RESEARCH ON THE PROBLEMS OF interaction BETWEEN SCIENCE AND RELIGION IN UNIVERSITY COURSE OF PHILOSOPHY (BASED ON WORKS BY RUSSIAN RELIGIOUS THINKERS) - Aleksey I. Belkin; Vasilе G. Gutsu; Svetlana N. Kontorovich (National Research Mordova State University, 2016)
Introduction: the article explores the interrelations between science and religion in the context of shaping integrated world outlook of future specialists in the framework of the competence-based approach. Axiological and ethical aspects of the interaction between the two major branches of human culture are considered using the example of works by Russian religious thinkers: Archbishop Luke (V. F. Voyno-Yasenetsky), V. S. Soloviev, N. A. Berdyaev. Materials and Methods: materials and methods: the study employed the method of original sources, i. e. works by N. A. Berdyaev, V. F. Voino-Yasenetsky, V. S. Solovyov, considering the problems of interaction between science and religion. The method of original sources was combined with methods of analysis, synthesis and generalisation. Results: attention is paid to different approaches to addressing this problem over the historical development of human thought. When analysing the works by V. S. Solovyov emphasis is made on the concept of integral knowledge, considering the true knowledge as a result of the interaction of rational, empirical and mystical aspects. Much attention is paid to the interpretation of Archbishop Luke's thoughts (V. F. Voyno-Yasenetsky) who advocated theoretically and practically the idea of the synthesis of the knowledge and belief in their inextricable link to the genuine scientific and philosophical works. When discussing N. A. Berdyaev's ideas the focus is on the critical analysis of the three types of relationships between science and religion, established in human culture: 1) supremacy of knowledge and denial of faith, 2) supremacy of faith and denial of knowledge, and 3) the dualism of knowledge and faith. The article also gives a thorough account of the philosopher's idea about the synthesis of knowledge, faith and intuition that contradicts traditional approach. The article presents the arguments of modern science about the importance of interaction between religious and scientific spheres of human culture. Discussion and Conclusions: the article highlights the importance of establishing harmonious relations between science and religion in the framework of axiological and ethical consideration of scientific and technological progress results. This approach allows to give an adequate response to many challenges of modern civilisation.